A remoção dos desastres e os desastres da remoção: risco, vulnerabilidade e deslocamento forçado em Belo Horizonte - Raquel de Mattos Viana (2015)
Each year in Brazil, during the rainy season and during periods of prolonged drought, tragedies with serious consequences in terms of human and material losses to the poorest and most vulnerable populations are reported. Given the average increase in global temperature and changes in weather patterns, along with Brazilian urbanization characteristics, the concept of 'environmental refugees` has been used to refer to the forced displacement of the population, generating debates in the academic arena on the adequacy of the concept and its ability to politicize/depoliticize the problem. Considering the relationship between forced displacement, extreme weather events and vulnerability, this dissertation aims, through a case study in the city of Belo Horizonte, Brazil, to understand some dimensions of environmental vulnerability in order to show responsiveness, resiliency and adaptive measures of the population. Inspired by the Age-Period-Cohort (APC) framework, this dissertation reviews the environmental vulnerability concept and its relation to forced displacement from these three dimensions of time. The method chosen was the multi-method which combines techniques of quantitative and qualitative research based on different sources of information. To draw a profile of natural disasters in Belo Horizonte and its metropolitan area the Damage Assessment Reports of Civil Defense were analyzed as well as some local newspaper reports related to these events during the first decade of this century. In order to understand the relationship between these events and the social and environmental vulnerability some socioeconomic and demographic indicators were collected. The analysis of secondary data showed that the most affected groups are children and the elderly and the population size and density are important dimensions of environmental vulnerability to disasters in the capital. Regarding the treatment of primary data, in depth interviews were conducted with residents of the former Vila Betânia, a small slum located on the banks of the Bonsucesso stream, in in west region of Belo Horizonte. This risky area was removed by the government in 2010. The interviews with residents and representatives of the municipal government enablead to understand the removal of these families and raised some hypotheses about the relationship between vulnerability and displacement in the light of a theoretical perspective on the transitions in demographic regimes.